Exploring the Anticancer Effects of Brominated Plastoquinone Analogs with Promising Cytotoxic Activity in MCF-7 Breast Cancer Cells via Cell Cycle Arrest and Oxidative Stress Induction - Ayse Tarbin Jannuzzi; Ayse Mine Yilmaz Goler; Nilüfer Bayrak; Mahmut Yıldız; Hatice Yıldırım; Betul Karademir Yilmaz; Deepak Shilkar; Raghusrinivasan Jayaprakash Venkatesan; Venkatesan Jayaprakash; Amaç Fatih TuYuN (MDPI AG, 2022)
Plastoquinone analogs are privileged structures among the known antiproliferative natural product-based compound families. Exploiting one of these analogs as a lead structure, we report the investigation of the brominated PQ analogs (BrPQ) in collaboration with the National Cancer Institute of Bethesda within the Developmental Therapeutics Program (DTP). These analogs exhibited growth inhibition in the micromolar range across leukemia, non-small cell lung cancer (EKVX, HOP-92, and NCI-H522), colon cancer (HCT-116, HOP-92), melanoma (LOX IMVI), and ovarian cancer (OVCAR-4) cell lines. One brominated PQ analog (BrPQ5) was selected for a full panel five-dose in vitro assay by the NCI's Development Therapeutic Program (DTP) division to determine GI50, TGI, and LC50 parameters. The brominated PQ analog (BrPQ5) displayed remarkable activity against most tested cell lines, with GI50 values ranging from 1.55 to 4.41 µM. The designed molecules (BrPQ analogs) obeyed drug-likeness rules, displayed a favorable predictive Absorption, Distribution, Metabolism, and Excretion (ADME) profile, and an in silico simulation predicted a possible BrPQ5 interaction with proteasome catalytic subunits. Furthermore, the in vitro cytotoxic activity of BrPQ5 was assessed, and IC50 values for U-251 glioma, MCF-7 and MDA-MB-231 breast cancers, DU145 prostate cancer, HCT-116 colon cancer, and VHF93 fibroblast cell lines were evaluated using an MTT assay. MCF-7 was the most affected cell line, and the effects of BrPQ5 on cell proliferation, cell cycle, oxidative stress, apoptosis/necrosis induction, and proteasome activity were further investigated in MCF-7 cells. The in vitro assay results showed that BrPQ5 caused cytotoxicity in MCF-7 breast cancer cells via cell cycle arrest and oxidative stress induction. However, BrPQ5 did not inhibit the catalytic activity of the proteasome. These results provide valuable insights for further discovery of novel antiproliferative agents.